Barriers to Lactulose Adherence in Patients with Cirrhosis and Hepatic Encephalopathy - Chow, Kenneth W.; Ibrahim, Brittney M.; Yum, Jung J.; Dang, An; Dang, Long; Chen, Kuan-Ting; Jackson, Nicholas J.; Saab, Sammy (Digestive diseases and sciences, 2023)
Background Hepatic encephalopathy (HE) is a major cause of mortality and morbidity in patients with cirrhosis. Lactulose non-adherence is one of the most frequently reported precipitants of hospital admission for HE. Aims We aimed to identify which factors contribute most to lactulose non-adherence and propose strategies to promote greater adherence and utilization of lactulose. Methods Participants in this study consisted of patients with cirrhosis who were taking lactulose for prevention of HE. Subjects were administered the Morisky Adherence Scale 8 (MAS-8) and a customized 16-question survey that assessed barriers to lactulose adherence. Results from the MAS-8 were used to stratify subjects into “adherent” and “non-adherent” groups. Survey responses were compared between groups. Results We enrolled 129 patients in our study, of whom 45 were categorized as “adherent and 72 were categorized as “non-adherent.” Barriers to adherence included large volumes of lactulose, high frequency of dosing, difficulty remembering to take the medication, unpleasant taste, and medication side-effects. Most patients (97%) expressed understanding of the importance of lactulose, and 71% of patients felt that lactulose was working to manage their HE. Hospital admission rates for HE was higher in non-adherent patients, although this difference was not statistically significant. Conclusion We identified several factors that contribute to lactulose non-adherence among patients treated for HE. Many of these factors are potentially modifiable. Patient and care-giver education are critical to assure adherence. Pharmacists and nurses are an essential but underutilized aspect of education regarding proper medication use.